Leadership as Experts by Experience in Professional Education. (13th May 2015) - Curran, Tillie; Sayers, Ruth; Percy-Smith, Barry
Abstract: Purpose: This paper shares the learning from a new course to explore and develop leadership by experts by experience involved in health and social care education provision, research and policy. Method: A Knowledge Café approach was used to provide opportunities for participants to explore and reflect together on shared experiences of what it means to be an expert by experience, and the extent to which the role can be understood in terms of grounded concepts of 'leadership'. Findings: The paper discusses how involvement as a service user emerged out of a personal drive to challenge and change appalling experiences of health and social care services. The paper goes on to illustrate this dynamic concept of leadership; the importance of networking with other users and carers, and, skills in enabling professionals to change. Argument and Conclusion: 'Professional leadership' is one of the domains of the UK Professional Capabilities Framework for social work defined as facilitated learning to include service users, carers and others involved.The call for a learning culture is not new and its application in complex practice and crisis points remains a current challenge. In contrast, the concept of Leadership discussed in this paper is grounded in experience and resonates with aspects of contemporary ethical, distributed and complex models of leadership but extends beyond organisations. Finally the paper raises the issue of learning opportunities available to experts by experience and the responsibilities for higher education and service providers to strengthen and support people in this complex role.